X chromosome control of meiotic chromosome synapsis in mouse inter-subspecific hybrids - Bhattacharyya, Tanmoy; Reifova, Radka; Gregorova, Sona; Simecek, Petr; Gergelits, Vaclav; Mistrik, Martin; Martincova, Iva; Pialek, Jaroslav; Forejt, Jiri (PLoS genetics, 2014)
Hybrid sterility (HS) belongs to reproductive isolation barriers that safeguard the integrity of species in statu nascendi. Although hybrid sterility occurs almost universally among animal and plant species, most of our current knowledge comes from the classical genetic studies on Drosophila interspecific crosses or introgressions. With the house mouse subspecies Mus m. musculus and Mus m. domesticus as a model, new research tools have become available for studies of the molecular mechanisms and genetic networks underlying HS. Here we used QTL analysis and intersubspecific chromosome substitution strains to identify a 4.7 Mb critical region on Chromosome X (Chr X) harboring the Hstx2 HS locus, which causes asymmetrical spermatogenic arrest in reciprocal intersubspecific F1 hybrids. Subsequently, we mapped autosomal loci on Chrs 3, 9 and 13 that can abolish this asymmetry. Combination of immunofluorescent visualization of the proteins of synaptonemal complexes with whole-chromosome DNA FISH on pachytene spreads revealed that heterosubspecific, unlike consubspecific, homologous chromosomes are predisposed to asynapsis in F1 hybrid male and female meiosis. The asynapsis is under the trans- control of Hstx2 and Hst1/Prdm9 hybrid sterility genes in pachynemas of male but not female hybrids. The finding concurred with the fertility of intersubpecific F1 hybrid females homozygous for the Hstx2(Mmm) allele and resolved the apparent conflict with the dominance theory of Haldane's rule. We propose that meiotic asynapsis in intersubspecific hybrids is a consequence of cis-acting mismatch between homologous chromosomes modulated by the trans-acting Hstx2 and Prdm9 hybrid male sterility genes.
Keywords: reprodukční izolace; Chromosome Pairing; lokus kvantitativního znaku; Infertility, Male; meióza; genetické lokusy; Synaptonemal Complex; mužské pohlaví; Mice; Quantitative Trait Loci; párování chromozomů; Reproductive Isolation; ženské pohlaví; synaptonemální komplex; zvířata; Humans; Meiosis; chromozom X; Hybridization, Genetic; hybridizace genetická; myši; histonlysin-N-methyltransferasa; mužská infertilita; Histone-Lysine N-Methyltransferase; Genetic Loci; Female; lidé; Male; X Chromosome; Animals